Traditional Expressions: A Folklore Study of Banjar People's Communication Patterns Based on History and Local Wisdom - Alfisyah, Alfisyah; Azkia, Laila (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2024)
As a collective culture passed down from generation to generation through oral tradition, folklore is still not widely known to the public. Even though the term folklore has been around for a long time, even long before the term culture, folklore is still considered a foreign science. In Indonesia, folklore studies and efforts to inventory various folklore have been carried out quite a lot, especially by James Danandjaya. However, until now there are still not many people doing Banjar folklore. This research found that the Banjar people's communication patterns are unique and have a local style. Traditional expressions contain many social, cultural, educational, economic, religious functions and values, outlook on life, leadership and even political values. This article aims to describe the various forms and functions of traditional expressions of the Banjar community or urang. The method used is descriptive qualitative, literature study and interviews. The results of the analysis show that the traditional expression urang Banjar has the function of softening sentences and as a medium for conveying criticism, advice and jokes.